Can trait competitiveness foster positive outcomes? The role of perceived insider status and leader competitiveness. (February 2023) - Xie, Songke; Meng, Xue; Li, Chaoping; Liu, Dege
Abstract: Drawing on self-representation theory, we explore how trait competitiveness affects innovative behavior and career satisfaction via perceived insider status and the boundary role of perceived leader competitiveness. Data were collected in two waves among 316 employees in China. The results showed that employee trait competitiveness was positively related to innovative behavior and career satisfaction via perceived insider status. These indirect effects were significantly stronger when working with competitive leaders and were insignificant otherwise. Our findings make theoretical contributions and practical implications regarding how, and under what circumstances, competitive employees will innovate and satisfy with their career development. Highlights: Employee trait competitiveness is positively related to innovative behavior and career satisfaction. Perceived insider status mediates these effects of employee trait competitiveness on work outcomes. The effects of employee trait competitiveness are stronger when working with a competitive leader.